Optimization of Nano-Hydroxyapatite Production from Limestone with Effect of Gelatin Concentration and pH in Sol-Gel Synthesis - S, Sutiyono; Edahwati, Luluk; Wahyudi, Mohammad Rafli Alif; Rahmah, Nazila Alfi (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
Nano hydroxyapatite is one of the biomaterials that has proven to be a very potential material due to its ability to bind directly with bone tissue. Limestone with a calcium carbonate content of 99.87% was used as a calcium source for the economical and sustainable synthesis of hydroxyapatite. The sol-gel method was chosen for the in situ gelatin synthesis process due to its ability to produce nanoparticles with high homogeneity. The particle size of nanohydroxyapatite can increase the surface area to volume ratio thus affecting the interaction with surrounding cells and tissues. Gelatin was added in various concentrations of 10%, 20%, and 30% as an innovative cell growth support modifier. The synthesis was also carried out at pH 9, 10, and 11 to evaluate its effect on hydroxyapatite formation. Optimal synthesis conditions were obtained at 30% gelatin concentration and pH 10, which resulted in the highest yield of 93.95%. Product characterization included Fourier Transform Infra-Red analysis, which showed the presence of typical hydroxyapatite functional groups (PO₄³-, OH-) and carbonate groups (CO₃²-). Scanning Electron Microscopy characterization showed nano-sized particles in the range of 443-578 nm with a granular structure. Porosity was found to be 72.52% making it ideal for cancellous bone tissue engineering applications.